Quantile Insights on Market Structure and Worker Salaries: The Case of Major League Baseball. (December 2019) - Fort, Rodney; Lee, Young Hoon; Oh, Taeyeon
The vast majority of the empirical investigation of player marginal revenue product (MRP) and monopsony exploitation rates (MER) implicitly assumed that MRP is constant across the revenue distribution of teams. The few works that do attempt to capture the impact of revenue variation across teams do so via independent variable specification. We bring quantile estimation to bear that allows MRP to vary across the entire revenue distribution in Major League Baseball. Completely in keeping with economic common sense, MRP increases as total revenue rises (to higher and higher quantiles). As with past findings, there is interesting MER dispersion over the length of player tenure in the league and between star and mediocre players. Heretofore unexplored, we also find interesting dispersion in MRP and MER between larger revenue and smaller revenue markets. Our results suggest that independent variable specifications overstate MRP and MER for smaller revenue teams and understate the same for larger revenue team.